2020
DOI: 10.36941/ajis-2020-0070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotional Intelligence, Interpersonal Communication and Job Satisfaction on the Job Performance of Staff in Chevron Nigeria Limited, Warri, Delta State Nigeria

Abstract: This study investigated the influence of emotional intelligence, interpersonal communication and job satisfaction on the job performance of staff in Chevron Nigeria Limited, Warri. Four null hypotheses guided the study. The correlation research design was adopted in the study. A sample of 400 was selected by the researchers using simple random sampling technique. The instrument used for data collection was a validated and reliable questionnaire. Regression statistics was used to test the stated null hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…HaI tersebut didukung oIeh hasiI peneIitian sebeIumnya yang diIakukan oIeh (Supriyanto & Troena, 2012) diperoIeh hasiI bahwa terdapat"pengaruh budaya terhadap kepuasan"kerja. Kemudian (Rozanna et aI., 2019), (Iestari & Wibawa, 2019), (Obiunu & YaIaju, 2020) menyatakan bahwa terdapat dampak yang siginifikan antara"kepuasan kerja terhadap kinerja"karyawan. Jika PT Matahari mengeIoIa"budaya organisasi maka karyawan akan puas kemudian memiIiki"kinerja yang tinggi daIam bekerja.…”
Section: F Pengaruh Budaya Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Sebagai Mediasiunclassified
“…HaI tersebut didukung oIeh hasiI peneIitian sebeIumnya yang diIakukan oIeh (Supriyanto & Troena, 2012) diperoIeh hasiI bahwa terdapat"pengaruh budaya terhadap kepuasan"kerja. Kemudian (Rozanna et aI., 2019), (Iestari & Wibawa, 2019), (Obiunu & YaIaju, 2020) menyatakan bahwa terdapat dampak yang siginifikan antara"kepuasan kerja terhadap kinerja"karyawan. Jika PT Matahari mengeIoIa"budaya organisasi maka karyawan akan puas kemudian memiIiki"kinerja yang tinggi daIam bekerja.…”
Section: F Pengaruh Budaya Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Sebagai Mediasiunclassified
“…An organization consists of communication units in hierarchical relationships between one another and functions in an environment [6]. Communication is the process of delivering a message by someone and another to inform or change attitudes, opinions, or behavior, either directly orally or indirectly through the media [4]. Communication can be concluded as a process of conveying messages by someone to change or shape the behavior of other people either verbally or through the media [19].…”
Section: Quality Of Communicationmentioning
confidence: 99%
“…The communication effectiveness variable is operationalized and measured by indicators described in 4 items obtained from the [20] study include: ease of obtaining information, accuracy in providing information, willingness to provide information, and openness in providing information [6]. The results of research by [4], [19] concluded that the quality of communication has a significant effect on job satisfaction.…”
Section: Quality Of Communicationmentioning
confidence: 99%
See 2 more Smart Citations